Service Quality Analysis of RFID-Based Smart Door Lock in Front One Azana Style Hotel Area - Putra, Fauzan Prasetyo Eka; Ramadhani, Nilam; Fauzan, Fauzan; Mursidi, Moh. (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
This research evaluates the service quality of an RFID-based smart door lock system in the Front One area of Azana Style Hotel Pamekasan. Employing qualitative analysis techniques, the study assesses the system's reliability, security, convenience, and responsiveness based on user experience and behavioral data. The primary goal is to understand how effectively the smart lock system enhances hotel services and operational efficiency. The findings aim to offer valuable insights to hotel management and the broader hospitality industry regarding the impact of smart technology on guest experience and hotel operations, thus fostering innovation and promoting environmental sustainability. By integrating RFID-based smart door locks with the Internet of Things (IoT), the system enables real-time access control, manages meeting room schedules, facilitates remote security monitoring, and oversees employee access management. This integration not only boosts service quality and operational efficiency but also creates a more connected and intelligent hotel environment. Consequently, the study highlights the potential of smart technology to transform hotel operations, improve guest satisfaction, and contribute to a sustainable future for the hospitality industry. Additionally, the research underscores the importance of continuous technological advancements in maintaining competitive advantage in the rapidly evolving hospitality sector, ensuring that hotels can meet the ever-changing needs and expectations of their guests.